Ɛ-polylysine coating with stinging nettle extract for fresh beef preservation. (June 2021) - Alirezalu, Kazem; Movlan, Hosein Shafaghi; Yaghoubi, Milad; Pateiro, Mirian; Lorenzo, José M.
Abstract: Combination effects of ɛ-polylysine coating (0.5 and 1%) and stinging nettle extract (3, 6 and 9%) on quality properties and shelf life of beef meat (2 × 2 × 2 cm) was evaluated at 4 °C for 12 days. The results indicated that ɛ-polylysine (ε-PL) coating with stinging nettle extract (SNE) had no significant effects on ash, fat, protein and moisture content among packaged beef samples in polyethylene bags (in atmosphere condition). At the end of storage, beef samples coated with 1% ε-PL and 9% SNE had significantly lower TBARS and TVB-N values compared to those found in control. Furthermore, 1% ε-PL coating with SNE 9% showed the highest inhibitory effects against molds and yeast, total viable counts (TVC) and coliforms during storage. However, sensory evaluation showed that samples coated with 1% ε-PL and 6% SNE had the highest scores for overall acceptability compared to the other groups. Based on the obtained results, ε-PL coating with SNE could be effectively used for extending the beef meat shelf life without negative effects on sensory attributes. Highlights: ɛ-PL coating as a new approach to deliver antioxidant and antimicrobial compounds ɛ-PL and SNE as useful ingredients for improving quality and shelf life of fresh beef Coating reduced microbial growth, lipid oxidation, TVB-N and improved sensory properties Safety and shelf life stability of fresh beef were extended by active ɛ-PL coating